Phenotypic characterization of Dagri cattle of Gujarat - PATEL, DINESH D; PATEL, ASHISH C; CHAUDHARI, DHAVAL F; JOSHI, R S; RANK, D N (The Indian Journal of Animal Sciences, 2021)
A hill cattle population locally known as Dagri reared by tribals from eastern border districts of Gujarat adjoining to Madhya Pradesh and Rajasthan, mainly Dahod and Chhotaudepur and to some extent Panchmahal, Mahisagar and Narmada was investigated for its phenotypic characterization. A total of 606 animals were examined for body measurements. Body weight of the newborn calf (4) and preweaning weight (24) were recorded by actual measurement on the weighing scale while, the body weight of animals above 1-year (606) was derived from body measurements using standard formula. Body measurements in males, females and heifers were taken on 606 animals. Milk composition was studied in milk samples from 50 cows. Draughtability was also studied on 11 pairs of bullocks. Dagri animals possessed predominantly white coat colour (males 95.45%; females 86.89%). Muzzle colour was mainly black (males 95.45%; females 91.59%). Eyelids were mainly black (males 100%; females 98.22%). Horn and tail switch were mainly black while hoof colour was mainly pale black. Horns were curved and oriented upward-outward. Forehead was straight. Ears were small oriented horizontally. Dagri cattle had small hump, dewlap and naval flap. The udder was bowl shaped, small sized with round tipped cylindrical teats and with no prominent milk vein. The means (cm) for chest girth, body length, height at withers and hip height were 134.40±4.03, 115.46±3.37, 106.66±2.11 and 109.13±1.84, respectively, in adult males and 128.93±0.35, 110.82±0.34, 102.46±0.28 and 104.99±0.26, respectively, in adult females. The means (cm) for face length, tail length, horn length, horn circumference, hump height, navel length, dewlap length, forehead width, ear length and ear width were 35.86±1.00, 67.33±1.37, 21.64±2.65, 18.00±0.85, 10.00±0.66, 05.87±0.54, 78.40±2.57, 15.66±0.54, 21.06±0.78 and 10.00±0.32 respectively in adult males and 35.95±0.10, 66.91±0.25, 19.26±0.29, 12.91±0.10, 06.98±0.06, 01.40±0.06, 72.86±0.35, 13.12±0.05, 19.23±0.11, 10.50±0.06 cm, respectively, in adult females. The mean body weight (kg) at different age groups, viz. birth weight, pre-weaning weight, body weight at 12 months, body weight at 24 months and adult weight were 16.75±0.25, 27.12±2.02, 60.02±19.85, 108.08±13.72, 223.85±14.70, respectively, in males and 13.0±1.0, 27.1±3.01, 66.5±7.16, 116.7±8.67, 169.63±1.21, respectively, in females. Reproduction traits, viz. age at first oestrus, age at first mating, age at first calving were 32 to 42, 42 to 48 and 48 to 60 months, respectively, in females. Production traits, viz. daily milk yield, lactation length and lactation milk yield were 1.75 kg, 120–240 days and 75–600 kg, respectively. These data were derived from farmers’ personal interview at their doorstep. Milk fat and SNF percentage were 4.08% and 9.18%. This lesser known population of hilly cattle was not recognized and registered as distinct breed before this investigation. This study played a major role in recognition and registration of this population. As a result of these efforts it is now recognized and registered as new cattle breed with accession no. INDIA_CATTLE_0400_DAGRI_03046.